RETAK TEMBOK DALAM KARYA SENI LUKIS - BANGKIT SANJAYA, Drs. Abd. Hafiz, M.Pd, Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2017)
The objective of this final work is visualized on society’s conflict which is metaphored by the wall cracked on cabbage complexion art painting.The methodology of this final work that is used by the writer are preparation, elaboration step, synthesis step, realization concept step, and final step. Therefore, the Writer wants to carry out of ten creations with the entitled: First, “Whispering”. Second, “Yelling”. Third, “The Impact of Conflict”. Fourth, “Smile, Angry and Scared”. Fifth, “Recrimination”. Sixth: “Fighting”. Seventh. “Twitting”. Eight, “Domestic Violence”. Ninth: “Egoism”. The tenth is “Spiteful”.Kata Kunci : Retak Tembok, seni lukis gaya kubisme.